TAX SYSTEMS OF THE MEMBER STATES OF THE EUROPEAN UNION - E. Bikas; G. Keliuotytė-Staniulėnienė (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
This article contains analysis of the tax systems of the member states of the European Union. Despite the numerous EU tax harmonization initiatives, national tax systems still have some differences. In order to evaluate these differences a comparative analysis of these tax systems is performed.